Exploring the antibacterial potential of environmental Pseudomonas aeruginosa isolates: Insights from in vitro studies and genome mining approaches - Md. Saddam Hossain; Afroza Aktar Sharna; Sumaiya Sharmin; Tahrima Arman Tusty; Abu Hashem; Palash Kumar Sarker (Journal of Genetic Engineering and Biotechnology)
Microorganisms are a significant source of antimicrobial agents, accounting for over half of the antibiotics used in healthcare today. This study focused on isolating and screening antibacterial microorganisms from soil samples, followed by a genome-based analysis of the most potent isolates. A total of 231 bacterial isolates were obtained from 63 soil samples collected across Dhaka, Sylhet, and Cox’s Bazar in Bangladesh. Among these, 51 isolates showed antibacterial activity in primary screening using the perpendicular streak method, while 28 exhibited activity in secondary screening via the agar well diffusion method against Escherichia coli ATCC35218, Staphylococcus aureus ATCC6538, Bacillus pumilus ATCC14884, Klebsiella aerogenes ATCC13048, Salmonella typhimurium ATCC13311, Pseudomonas aeruginosa ATCC9027, Micrococcus luteus ATCC10240, B. cereus ATCC10876, Proteus vulgaris ATCC8427, and B. subtilis ATCC6633. All primary screening positive isolates were identified via 16S rRNA analysis, revealing eight genera: Streptomyces (5), Sinomonas (1), Nocardiopsis (3), Arthrobacter (1), Micrococcus (1), Pseudomonas (27), Microbacterium (1) and Bacillus (6). The top five most promising isolates were identified as Pseudomonas aeruginosa, exhibiting strong antagonistic activity, and underwent whole-genome sequencing. Genome mining revealed multiple biosynthetic gene clusters (BGCs), indicating the production of known and unknown antimicrobial compounds, including Pf-5 pyoverdine, Azotobactin D, Pyochelin, and Pyoverdine SMX-1. This study is the first to combine whole-genome analysis with antibacterial activity assessment, highlighting Pseudomonas aeruginosa as a prolific source of bioactive secondary metabolites.